(untitled) - Gnap, Jozef; Rolko, Peter (Doprava a spoje, 2006)
In the article, the authors analyze a price development in highway freight trasportion within the last few years. The price development of transport relations is analyzed from the point of view of the trasnsporters working at the slovak market.